2020
DOI: 10.3390/polym12020386
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Low-Frequency Induction Heating Effect of Magnetic Composites for Medical Applications

Abstract: This study aims to enhance the low-frequency induction heating (LFIH) effect in a thermoplastic polymer doped with iron oxide magnetic particles, which are promising candidates for several medical applications thanks to their confirmed biocompatibility. Two main approaches were proposed to successfully boost the heating ability; i.e., improving the magnetic concentration of the composite with higher filler content of 30 wt %, and doubling the frequency excitation after optimization of the inductor design. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Especially, our experiment revealed that the Fe 3 O 4 nanopowder exhibits negative susceptibility in the X-band while it shows superparamagnetism at low frequencies [6][7][8][9] . A similar phenomenon was observed on La 0.7 Sr 0.3 MnO 3 nanocomposites 10 and FeNi 3 /C nanocapsules 11 .…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Especially, our experiment revealed that the Fe 3 O 4 nanopowder exhibits negative susceptibility in the X-band while it shows superparamagnetism at low frequencies [6][7][8][9] . A similar phenomenon was observed on La 0.7 Sr 0.3 MnO 3 nanocomposites 10 and FeNi 3 /C nanocapsules 11 .…”
mentioning
confidence: 73%
“…The value of Ŵ f is expected to be constant. (8) give us m r for any direction of the external magnetic field. However, the orientation is randomly distributed in the experiment.…”
Section: Permeabilitymentioning
confidence: 99%
“…The operating frequency applied for radio frequency induction heating is usually higher than 20 kHz and in less than 1 MHz, depending on the application. And at frequencies below 100 kHz, the skin depth is large, which makes it inefficient to apply to nanomaterials [ 37 , 47 ]. Therefore, three frequency systems were selected within that frequency range to investigate the effect of induced power and frequency on the change in sheet resistance of the Ag NW network.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrates that by increasing the operating frequency of the magnetic source, it is possible to achieve a higher temperature with a faster response time. [3,32] Particle alignment during fabrication clearly shows enhancement in thermal and magnetic anisotropy. [4] Future works aim to optimize the material and process so as improve the heating effect and thermal transfer.…”
Section: Toward Medical Applicationmentioning
confidence: 99%
“…The LFIH test results of the printed cubic sample under the horizontal array and Halbach array are shown in Figure . An experimental test bench was described in previous work, [ 32 ] where the 16‐magnet inductor was used to generate a 4200‐Hz magnetic field. It is expecting that the temperature response is the most significant in the preferred direction ( y ‐axis) and the lowest in the z‐direction, regardless of either Halbach or horizontal array, is used during the printing process.…”
Section: Characterization Of Induction Heating and Magnetic Propertiesmentioning
confidence: 99%